Agronomy of black pepper (Piper nigrum L.) - a review - K THANKAMANI, K SIVARAMAN, K KANDIANNAN, K V PETER, C (Journal of Spices and Aromatic Crops, 1999)
Black pepper (Piper nigrum L.), a highly valued spice crop, is a perennial vine which originated in the Western Ghats of India and subsequently spread to other countries. Various aspects of crop ecology and agronomical practices such as planting material production, spacing and supports, training and pruning, irrigation, mulching and weeding, nutrition, harvest and cropping systems are reviewed.